Lying in Arthur Miller's The Crucible: A Pragmatic Study: هديل محمود إبراهيم , جمعه قادر حسين (Journal of the College of Education for Women, 2021)
Lying is a controversial issue as it is closely related to one's intended meaning to achieve certain pragmatic functions. The use of lying in literary works is closely related to the characters’ pragmatic functions as in the case of Miller's The Crucible where it is used as a deceptive complex phenomenon that cannot be observed out of context. That is, the use of lying as a deceptive phenomenon represents a violation to Grices's Maxims. Thus, the study aims to qualitatively examine the kinds of maxims being violated, the kinds of violations conducted, the strategies followed in the violations, and the pragmatic functions behind such violations across the different categories of lies. To this end, the (30) extracts found in Miller's The Crucible have been all examined following Grice's (1975/1978) Cooperative Principle and Implicature theories. The analysis has revealed that the quality maxim was breached most of the time with a percentage of (96,6~97%), covert violation occupied (66,6~67%) (the same percentages of both prototypical lies and Intentional Deceptive Lies), fabrication was with (83%) and the pragmatic function ''to avoid punishment'' appears with (46,6~47%). This means that truthfulness was violated beside other maxims, and strategies of fabrication. Such a violation enhances lying, and false-implicature, and intensifies the tragic end for most of the innocent characters. Minor lies are slightly concerned with plot development and events escalation. Finally, the characters lie in order to achieve certain pragmatic functions. However, the most dominant function adopted when lying was to avoid punishment.